Lumbosacral intraspinal extradural ganglion cyst in a cat - Francesca de Strobel (Journal of Feline Medicine and Surgery Open Reports, 2015)
Case summary A 16-year-old neutered female domestic shorthair cat was referred for chronic history of reluctance to jump, stiffness of the tail and lower back pain. Mild pelvic limb ataxia, reduced perianal reflex and lumbosacral discomfort were present on neurological examination. On magnetic resonance imaging, a well-defined rounded structure of 3 mm in diameter was identified on the right dorsal aspect of the epidural space at L7–S1, causing displacement of the cauda equina. The lesion was hyperintense to spinal cord parenchyma on T2-weighted images and hypointense on T1-weighted images, consistent with a fluid-filled structure. A Lumbosacral dorsal laminectomy was performed. A clear fluid-containing structure was identified between the right L7 nerve root and the cauda equina. Following surgical excision, histopathology confirmed the cystic nature of the lesion and revealed thick disorganised sheaths of fibrocollagenous tissue and flattened mesenchymal cells lining the luminal part of the cyst wall. A diagnosis of intraspinal ganglion cyst was made. The cat recovered uneventfully. Seven months after surgery euthanasia was performed for unrelated reasons; no neurological deficits were present. Relevance and novel information This is the first reported case of intraspinal ganglion cyst in a cat. Intraspinal extradural cysts should be considered among other differential diagnoses for cats with lumbosacral myelopathy/radiculopathy.